Long-term dynamics of cytomegalovirus-specific antibodies in a longitudinal cohort of children followed up for the first decade of life - Mburu, Maureen W.; Safari, Mercy S.; Makori, Timothy O.; Gicheru, Elijah T.; Nyawa, Omar K.; Kuria, Timothy Chege; Foley, Deirdre J.; Sande, Charles J. (Scientific Reports, 2025)
Cytomegalovirus (CMV) causes infections that last a lifetime and are primarily contracted in childhood. Congenital transmitted CMV is associated with severe neurological sequelae and can cause life-threatening disease in immunocompromised individuals. Although antibodies are generally presumed to correlate with protection, their long-term dynamics remain poorly understood. We aimed to determine the longevity of CMV-specific antibodies in a low-income setting in Kilifi County, Kenya. To track long-term antibody dynamics, we conducted longitudinal surveillance of annually collected serum samples and assayed for antibodies against the CMV tegument phosphoprotein (pp150). The duration of effective immunity against re-infection was estimated using piecewise regression modelling. Serum antibody to CMV was measured in 123 children recruited within the first five years of life and sampled annually over a median of 10 years (range: 7–14). Antibodies to the CMV pp150 showed a cyclic trend of acquisition and loss at the population level. Individually, we observed early antibody acquisition, followed by decline and rebound. Regression analysis identified a 7.57-year inflection point in antibody trajectories, marking a transition from waning to re-accumulation - potentially reflecting natural boosting events in a population where CMV infection occurs early in life. The data show a clear pattern of early natural infection, followed by repeated patterns of antibody acquisition, loss, and re-acquisition over the first decade and a half of life.
CRIS-Team Scopus Importer:2025-10-24
Keywords: Antibody kinetics; Children; Cytomegalovirus (CMV); Longitudinal analysis; Sub-Saharan africa